Transparent Conductive Oxides and Their Applications in Near Infrared Plasmonics. Issue 5 (27th February 2019) - Wang, Zhewei; Chen, Chaonan; Wu, Ke; Chong, Haining; Ye, Hui
Abstract : Transparent conductive oxides (TCOs) have been widely used as an important component of optoelectronic devices. They are required to exhibit high performance in both visible‐range transparency and electronic conductivity simultaneously. In near infrared (NIR) wavelength, these highly doped semiconductor oxide materials exhibit a drop in their real part of dielectric permittivity from positive to negative. In other words, the epsilon‐near‐zero (ENZ) frequency of TCO is located in NIR spectral regime. On the other hand, the imaginary part of the permittivity is relatively low which implies less optical loss when compared to noble metals. This "metal‐like" permittivity dispersion characteristic of TCOs means their capability to support surface plasmons (SPs) in the NIR regime. In this paper, a summary of various physical parameters of commonly used TCOs such as ITO, AZO, and FTO, etc., is given. These parameters include carrier density, carrier mobility, plasma frequency, and ENZ wavelength. The difference among these parameters determines their diverse performance in infrared range. In this paper, the important role of TCOs for applications in the NIR/IR wavelength ranges are reinforced, as they are demonstrated in the visible range. Abstract : Transparent conductive oxides (TCOs) possess good transparency and conductivity simultaneously in visible range. Their epsilon‐near‐zero (ENZ) wavelengths happen to fall in near infrared region, making them candidates for NIR surface plasmon polarion materials. A summary of various physical parameters for commonly used TCOs is provided in this review article. The difference among these parameters determines their diverse performance in infrared plasmonics.